The Role of Muse from Influencers in Increasing the Buying Interest of Gisca Make Up Consumers - Aisyi, Gisca Faradista Filla; Muslih, Basthoumi (Universitas Nusantara PGRI Kediri, 2025)
Research aim : The purpose of this study is to exploring how consumers respond to the muse from influencers used by Gisca Make Up so as to increase their buying interest. Design/Method/Approach : This study uses a descriptive qualitative approach and the techniques used are interviews, observations, and documentation by applying informant selection techniques according to age and 5R (reach, relevance, resonance, reaction, retention). The informants of this study were three consumers of Gisca Make Up in 2024. The data analysis technique used the theory of Miles and Huberman which includes data analysis steps including data collection, data reduction, data presentation, and drawing conclusions/verification. Research Findings : The branding carried out by Gisca Make Up on social media by using muses from influencers is very easily accessible to young and adult communities as consumers but not yet comprehensive, because there are some elderly people who do not access the media so that social media branding is not very effective to use. To increase buying interest among consumers, Gisca Make Up must also continue to do branding with offline media such as using banners and pamphlets, the branding can run smoothly and can be reached comprehensively by all consumers from young, adult, to elderly. The muse used must have good visuals and personal branding. In addition, good products and in accordance with consumer desires also make the quality of Gisca Make Up. Theoretical contribution/Originality : There has not been much research in the area related to MUA services. Practitioner/Policy implication : Useful as a way of branding MUA services in the area and its surroundings. Research limitations: The limitations of this research are due to the limited time and samples taken.